Effect of Organizational Agility on Performance of Commercial Banks in Nairobi City County, Kenya - Samo, Yona; Wanyama, Kadian; Okonda, Michael (International Journal of Strategic Management, 2025)
Purpose: To examine the effect of organizational agility on the performance of commercial banks in Nairobi City County, Kenya, in the context of adapting to market changes and evolving customer demands and regulatory requirements. Methodology: The research employed a mixed-methods design that integrated both quantitative and qualitative approaches to explore the relationship between organizational agility and bank performance in Nairobi City County, Kenya. Quantitative data was collected using structured questionnaires administered to 108 branch and operational managers, focusing on variables such as organizational agility and bank performance. Additionally, qualitative insights were gathered through semi-structured interviews with 38 Chief Executive Officers, which facilitated an in-depth examination of strategic flexibility practices. Participants were selected through stratified random sampling, resulting in a high response rate. The data collection process adhered to ethical guidelines and included a pilot study to ensure the instruments' reliability and validity. Quantitative analysis consisted of descriptive statistics, correlation, and regression analyses, while qualitative data were thematically analyzed to provide comprehensive insights. Findings: The findings on organizational agility in commercial banks in Nairobi City County reveal a high level of adaptability among respondents, with quantitative data collected via eight questionnaire items demonstrating significant agreement across various aspects of agility. The statement with the highest mean score of 4.19 (SD = 0.76) emphasized the bank's focus on actively seeking and valuing customer feedback, while the lowest mean of 4.03 (SD = 0.79) indicated potential improvements in decision-making speed related to organizational structure. Overall, all mean scores exceeded 4.00, confirming a strong perception of organizational agility. Additionally, a simple linear regression analysis illustrated that organizational agility significantly predicts bank performance, with an R-value of 0.681 and an R-squared value of 0.464, indicating that it explains 46.4% of the variance in performance. The unstandardized coefficient for organizational agility was 0.625 (SE = 0.049), suggesting that a one-unit increase in agility is associated with a 0.625-unit improvement in performance. Qualitative interviews with bank executives and managers further supported these findings, emphasizing that organizational agility directly translates into better financial performance and customer satisfaction, thus reinforcing the critical role of organizational agility in enhancing performance within the competitive banking environment. Unique Contributions to Theory, Practice and Policy: The study provides valuable insights for banking executives by highlighting the importance of organizational agility in enhancing responsiveness to market changes. Regulatory bodies can leverage these insights to formulate policies that support the adaptability and resilience of the banking sector. The findings encourage academic researchers to further explore the theoretical connections between strategic management and dynamic environments, thus contributing to the academic discourse on strategic flexibility. Key recommendations for commercial banks emphasize the need to prioritize the development of organizational agility to improve their responsiveness to market changes.